The effect of growing season on growth rate, pod partitioning, phenology and yield variations of mungbean varieties - HERDINA PRATIWI; AGUSTINA ASRI RAHMIANNA (Smujo International, 2017)
Pratiwi H, Rahmianna AA. 2016. The effect of growing season on growth rate, pod partitioning, phenology and yield variations of mungbean varieties. Nusantara Bioscience 9: 243-250. The primary objective of mungbean improvement program is the production of high yielding varieties, which is influenced by physiological trait of variety or genotype and environment. The present research aimed to study the effect of growing season on growth rate, pods partitioning, phenology and yield variations of several mungbean varieties. Field experiments were conducted at Muneng Experimental Station of the Indonesian Legume and Tuber Crops Research Institute (ILETRI), Probolinggo District, East Java, Indonesia during rainy season (October to December 2011), and dry season (May to July 2012). A randomized complete block design was employed in the present study consisted of mungbean varieties as treatments in each growing season, and three replicates. The treatments were superior mungbean varieties, i.e. Vima 1, Sriti, Murai, Kutilang and Fore Belu. The observed variables were plant phenology, plant growth rate, seed yield and yield attributes. The results indicated the growing season affected plant growth rate, pod partitioning, phenology and seed yield and yield components with rainy season influenced more parameters of plant growth rate, crop phenology, seed yield and its components as compared to dry season. Conversely, dry season had more effect on pod partitioning coefficient, total dry biomass rate, and seed size. There was significant interaction effect of genotype by growing season on total dry matter and pod growth rates, days to flowering, days to pod maturity, plant height, seed yield, plant population, pod weight, and 1000-seed weight. Seed yield varied among seasons and varieties with the average seed yield in rainy season was 75 to 119% higher than those in dry season except Fore Belu that had the same yield in both seasons.